First Clinical Evidence About the Use of a New Silver-Coated Titanium Alloy Instrumentation to Counteract Surgical Site Infection at the Spine Level - Lucrezia Leggi; Silvia Terzi; Maria Sartori; Francesca Salamanna; Luca Boriani; Emanuela Asunis; Cristiana Griffoni; Gianluca Giavaresi; Alessandro Gasbarrini (Journal of Functional Biomaterials)
Background: Surgical site infections (SSIs) following spinal instrumentation surgery are among the most concerning complications. This study is aimed at assessing the effectiveness of a new treatment approach for SSIs that includes a single-stage approach with the removal of the previous hardware, accurate debridement, and single-stage instrumentation using a silver fixation system (SFS) made of titanium alloy coated with silver (Norm Medical, Ankara, Turkey) by means of a retrospective observational study. Materials and Methods: The demographic data, type of surgery, comorbidities, pathogens, and treatment details of consecutive patients with an SSI who received the SFS between 2018 and 2021 were extracted from their medical records and analyzed. The patients treated with the SFS for primary pyogenic infections were excluded. The patients were re-evaluated at multiple endpoints in order to assess the rate of reinfection and the local and general complications. Results: Fifty-six patients were treated with the SFS and thirty-four patients met the inclusion criteria. Out of those 34 patients, the rate of infection recurrence or insurgence after the implantation of the SFS was 11.8%, with infection detected in 4 out of 34 cases and mechanical problems detected in 2 of the 34 cases (5.9%). The overall success rate in controlling infection recurrence or emergence was 88.2% (30 out of 34 cases). The overall survival rate of the SFS was 87%, 78%, and 71% at one, two, and three years, respectively. Conclusions: The surgical strategy with the SFS demonstrated promising outcomes in preventing infection recurrence or insurgence, with a low incidence of mechanical complications. However, further structured and comprehensive studies are essential for validating these initial findings.